Computational Simulation and Experimental Analysis of Activated Carbon from Agricultural Waste as Electromagnetic Absorber - Nawrah Afnan Ashraf; Fadzidah Mohd Idris; Noorain Purhanudin; Syahida Suhaimi; Intan Helina Hassan (Semarak Ilmu Publishing, 2024)
Indexed by Scopus